Economic forest Resources of Garhwal-kumaun Himalaya - Negi, P. S. (Indian Forester, 1992)
The economic forest resources of the Garhwal-Kumaun Himalaya (Uttrakhand) has been explored in the present paper with special reference to medicinal and other economic plants which may be used to boost the economy of the region and in providing local employment. Since the principal climatic factors are influencing mountain vegetation, therefore, the paper also throws light upon those factors whose study would be useful in reflecting more clear and distinctive idea about the areas of the study.